Banking performance and the business cycle: empirical evidence from Greece. (2015) - Vogiazas, Sophocles; Alexiou, Constantinos
This study aims at enhancing our understanding on the factors that condition bank profitability in the context of the Greek banking sector. In this direction panel data analysis has been used and effectively applied on 17 Greek banks over the period 2004-2010.The results generated suggest that key variables - such as solvency, non-performing loans and cost-efficiency play an instrumental role in explaining banks' profits. The strength of a bank's balance sheet is among the primary indicators of solid performance whilst at the same time banks' profits or losses appear to be time persistent. Given the sample's diversity, it is not surprising that linkages between economic conditions and bank performance tend to be more evident at an aggregated, dynamic level. However, the results suggest that regaining profitability after a recession or a period of adverse economic conditions may prove a painful process, given the significance of business cycle variables in explaining banks' performance.